Occupational health problems among migrant and seasonal farm workers. - Mobed, K (1992)
Migrant and seasonal farm workers are one of the most underserved and understudied populations in the United States. The total US population of such farm workers has been estimated at 5 million, of whom about 20% live or work in California. Farm workers perform strenuous tasks and are exposed to a wide variety of occupational risks and hazards. Low socioeconomic status and poor access to health care also contribute to existing health problems in this population. Potential farm work-related health problems include accidents, pesticide-related illnesses, musculoskeletal and soft-tissue disorders, dermatitis, noninfectious respiratory conditions, reproductive health problems, health problems of children of farm workers, climate-caused illnesses, communicable diseases, bladder and kidney disorders, and eye and ear problems. Few epidemiologic studies exist of these occupational health problems. No comprehensive epidemiologic studies have assessed the magnitude of occupational health problems among migrant and seasonal farm workers and their dependents. Although the migratory nature of this population makes long-term studies difficult, the development of standardized data collection instruments for health consequences and scientific assessment of farm work exposures and working conditions are vital to characterize and reduce the occupational health risks in farm workers.